UPAYA MENINGKATKAN KEDISIPLINAN BELAJAR MATEMATIKA DAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN ROLE PLAYING PADA SISWA KELAS VIII D SMPN 14 MADIUN - Tantri Darmasari; Rudi Santoso Yohanes (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2019)
This research was aimed to know how was the effort to increase learning achievement in Math for grade VIII D SMPN 14 Madiun using Role Playing method. From this research that has been done bring some conclusions that are: 1. The average of total result teacher’s ability using Role Playing method in cycle I is 2,69 with good category had been increase in cycle II 3,00 with good category. This already accomplished success indicator that has been determined. 2. The percentage of students’ learning discipline in Math during learning process in cycle I 23,1% for not good category and 76,9% for good enough category, it was increased in cycle II 25% for good category and 75% for good enough category, but this hadn’t accomplished success indicator that has been determined. 3. Learning achievement test, average score of students’ learning achievement in Math cycle I 47,8 with 3 student completed and in cycle II 68,42 with 10 students completed. It shows that students learning achievement in Math has been increase but not accomplish the success indicator yet. Learning process using Role Playing in this research could increase students’ learning discipline in Math, but it increased step by step.